2012
DOI: 10.1016/j.electacta.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic activity and durability of Pt/NbO2 and Pt/Ti4O7 nanofibers for PEM fuel cell oxygen reduction reaction

Abstract: a b s t r a c tIn this paper, we report the synthesis of both NbO 2 and Ti 4 O 7 nanofibers using an electrospinning technique in an effort to use metal oxides as a possible replacement for carbon as PEM fuel cell catalyst supports. The synthesized nanofibers are physically characterized using several methods including XRD, SEM, TEM, BET, ICP-MS as well as XPS. The thermal, chemical, and electrochemical stabilities as well as the electronic conductivities of these two supports are also evaluated in order to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Pt/TiO 2 -CNx displayed higher activity than Pt/C, which may be due to the higher amounts of active sites provided by Pt nanoparticles and high electric conductivity of CNx nanowires for the oxygen reduction reaction than Pt/C (Fig. 5); moreover, some TiO 2 particles became Ti 4 O 7 , which significantly [36]. The BET specific surface area is calculated to be 131.677 m 2 /g for Pt/TiO 2 -CNx; however, the Pt/C catalyst has a high BET surface area of 208.871 m 2 /g.…”
Section: Resultsmentioning
confidence: 94%
“…Pt/TiO 2 -CNx displayed higher activity than Pt/C, which may be due to the higher amounts of active sites provided by Pt nanoparticles and high electric conductivity of CNx nanowires for the oxygen reduction reaction than Pt/C (Fig. 5); moreover, some TiO 2 particles became Ti 4 O 7 , which significantly [36]. The BET specific surface area is calculated to be 131.677 m 2 /g for Pt/TiO 2 -CNx; however, the Pt/C catalyst has a high BET surface area of 208.871 m 2 /g.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, niobium dioxide (NbO 2 ) with electronic configurations of 4d 1 has abstracted increasing attention [22,23]. Orilall et al [24] reported that Pt-Pb nanoparticles incorporated into mesoporous NbO 2 -carbon composites showed high mass activity toward formic acid electrooxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon black is a commonly used support in fuel cells, but the corrosion of the carbon support would cause a negative impact on the working efficiency and performance of fuel cells [14]. Recently, Ti 4 O 7 has been found to be a promising support material owing to its higher corrosion resistance and superior electrical conductivity than carbon black [15]. In our previous work [16], it is shown that Pt catalyst supported on Ti 4 O 7 possesses better catalytic activity and stability than Pt catalyst supported on carbon black and commercial TiO 2 for formic acid electrooxidation.…”
Section: Introductionmentioning
confidence: 99%